Analyzing the logistic process for pre-engineering building (P.E.B) construction - Le Khac Bao; Chotchai Charoenngam; Hadikusumo, Bonaventura H. W.; Huynh, Trung Luong (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Erection is the last important stage of P.E.B product life cycle, to complete success this stage, it is requested the fulfillment of previous stages as the erection logistic stage. However, in the real erection job sites, especially the job sites in Vietnam, there a lot of problems happened in this stage that make erection stage can not be completed as expected, by analyzing to find out the root causes of these problems from the data, which are investigated from a real P.E.B company, base on key relevant theories, the Author would like to develop the solutions for future improvements.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Construction Engineering and Infrastructure Management
Project (M. Eng.) - Asian Institute of Technology, 2009
Keywords: Construction industry -- Vietnam